Does Workplace Friendship Contribute Toward Work Engagement among Employee of West Java’s Industrial Area? - Diah Zaleha Wyandini; H.M Engkos Kokasih; Intan Faridah (Program Studi Psikologi UIN Sunan Ampel Surabaya, 2023)
Organization needed energetic and dedicated employees, employees who are engaged with their work. But some surveys show that engagement among employee specially millennials tend to be decreased. One of the factors can contributed toward work engagement is workplace friendship. This study aims to examine whether workplace friendship contribute toward work engagement among employee in the industrial area of ​​West Java. The participants involved were 409 employees in the industrial area of ​​West Java (Bekasi, Karawang, Purwakarta, and Bandung Raya) with a minimum working period of one year or more. The instruments used in this study were the Workplace Friendship Scale (WFS) to measure workplace friendships with a reliability of 0. 687 and The Utrecht Work Engagement (UWES) to measure work engagement with a reliability of 0.929. The data analysis technique used is simple linear regression analysis using the SPSS version 26 program. The results show that workplace friendship contribute toward work engagement among employee in the industrial area of West Java